Current problems of rubberwood in furniture industry / Suhaimi Ramly - Ramly, Suhaimi (2004)
Rubberwood as an important agriculture plantation in Malaysia early it was introduced until now. Hevea brasiliensis is the scientific name for the rubber tree which has classification in group C as a light hardwood. Today Rubberwood is the most important material that used by furniture manufacture to produce their product. However, several problems happened during the processing and producing their product The manufacturer must take the alternative ways to solve their problem before it getting bigger or it will give effect the Furniture Industry in Malaysia.